2018
DOI: 10.1037/adb0000425
|View full text |Cite
|
Sign up to set email alerts
|

Slot machine gambling and testosterone: Evidence for a “winner–loser” effect?

Abstract: The “winner–loser effect” refers to a phenomenon in testosterone research where the outcome of a social competition induces increases (wins) and/or decreases (losses) in testosterone levels. Here, we sought to test to what extent changes in testosterone occur in response to gambling behavior. More specifically, we hypothesized that the winner–loser effect would extend to slot machine gambling as a solitary (noncompetitive) gambling activity in players who “anthropomorphized” the slot machine, thus treating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 207 publications
(336 reference statements)
0
3
0
Order By: Relevance
“…A study found that testosterone significantly increased during a one-on-one poker competition, while outcomes of the gambling competition did not affect testosterone levels (Steiner et al, 2010). A more recent study not only supports these findings, but also suggests that such effects could be extended into a slot machine gambling task in healthy male subjects (Ferrari et al, 2018). Taken together, these results clearly suggest that increased levels of testosterone in healthy subjects are related to higher risk taking or to higher impulsive propensity that relate to gambling behavior.…”
Section: Testosterone and Gambling/gambling Behaviormentioning
confidence: 90%
“…A study found that testosterone significantly increased during a one-on-one poker competition, while outcomes of the gambling competition did not affect testosterone levels (Steiner et al, 2010). A more recent study not only supports these findings, but also suggests that such effects could be extended into a slot machine gambling task in healthy male subjects (Ferrari et al, 2018). Taken together, these results clearly suggest that increased levels of testosterone in healthy subjects are related to higher risk taking or to higher impulsive propensity that relate to gambling behavior.…”
Section: Testosterone and Gambling/gambling Behaviormentioning
confidence: 90%
“…Participants were recruited to three experiments conducted between 2015 and 2018 (N 1 = 121, age M = 21.25, SD = 2.91; N 2 = 80, age M = 20.55, SD = 2.37; N 3 = 106, age M = 20.80, SD = 2.39, Figure 1). Primary analyses for Studies 1 and 2 are already published (Ferrari et al, 2018;Murch and Clark, 2019), without the measures of PEP. Study 3 has not been submitted for peer-reviewed publication (Murch, 2016).…”
Section: Participantsmentioning
confidence: 99%
“…As opportunities to gamble have increased over the last several years, accordingly the number of gambling studies has also grown (Dixon et al, 2015). Researchers from different disciplines, such as psychology (Ferrari et al, 2018;Hodgins et al, 2016), health (Williams & Volberg, 2014), and neuroscience (Yücel et al, 2017), have investigated gambling mainly from psychological and medical perspectives. A small number of gambling studies are produced by researchers from other academic disciplines, such as economics (Tymula & Whitehair, 2018) and business (Prentice & Zeng, 2018).…”
Section: Introductionmentioning
confidence: 99%